ANALISIS KEPUTUSAN WANITA DALAM BERWIRAUSAHA (Studi Pada UKM Posdaya Binaan STIE Malangkucecwara Malang) - Siti Munfaqiroh (Adbis: Jurnal Administrasi dan Bisnis, 2018)
The role of entrepreneurship in development is able to absorb labor so that it will have an impact on a country's economic growth. For this reason, the role of entrepreneurship must continue to be developed in order to increase the country's economy and national security and not be dependent on other countries. This shows that small businesses can be used as an opportunity for people to create jobs. . The objectives in this study are: (1) To examine the partial effect between capital factors, independence and family factors on entrepreneurship in entrepreneurship? (2) To examine the simultaneous effect between capital factors, independence and family factors on women in entrepreneurship. The population in this study was UMKM Posdaya under the guidance of STIEMalangkucecwara. The results show that there is a significant and simultaneous influence between capital factors, independence and family factors on entrepreneurship in business people. Furthermore, which has the greatest influence is the capital factor variable that is equal to 0.522